Kepemimpinan Transformasional Kepala Sekolah dalam Penguatan Disiplin Peserta Didik di MA Darussalam Ngesong, Jombang - Permana Permana; Moh. Syamsul Falah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the forms of student discipline and provides a description of efforts to improve student discipline. This qualitative descriptive study focuses on the school principal, teachers, students, and staff as primary informants. The primary focus of this study is the school principal’s leadership role in enhancing student discipline. Data collection methods included interviews, observations, and document analysis. The results of the observation reveal that 1) The leadership style of the principal at MA Darussalam Ngesong Jombang is democratic in nature; that is, the principal acts as a leader who is friendly, highly disciplined, intelligent, firm, and possesses a clear visionary direction. This can also be seen from various sources of information or members of the school community who observe the principal’s daily routines, such as arriving earlier than teachers and students, always being friendly to all members of the school community, and consistently greeting everyone with a smile and a warm welcome. 2) MA Darussalam Ngesong Jombang has various discipline programs within its extracurricular activities. These programs can lead to improved academic performance among students. However, there are still some areas that need improvement, such as tardiness and incomplete uniform compliance. 3) Various methods for improving discipline, according to E. Mulyasa, involve implementing student discipline strategies such as fostering self-concept, communication, integration, and the alignment of attitudes within learning activities.